1985
DOI: 10.1002/chin.198501022
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SOLID STATE TRANSFORMATIONS DURING COOLING IN THE NICKEL‐RICH PORTION OF THE NICKEL‐SILICON SYSTEM

Abstract: DTA‐, XRD‐, SEM‐ und TEM‐Untersuchungen an Legierungen mit 10‐35 Atom‐% Si zeigten, daß rasche Abkühlung zur Bildung von γ‐Ni5Si2 führt, das metastabil ist und bei hohen Temp. nur langsam zerfällt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…1b. Similar observations have been reported in the nickel-rich Ni-Si binary alloys [19]. Detailed microstructural observations showed that these precipitates exhibited two characteristic morphologies (cuboids and spheroids) coherent with the Ni (α) matrix as depicted in the micrograph of Fig.…”
Section: Precipitations In the Ni (α) Solid Solutionsupporting
confidence: 86%
“…1b. Similar observations have been reported in the nickel-rich Ni-Si binary alloys [19]. Detailed microstructural observations showed that these precipitates exhibited two characteristic morphologies (cuboids and spheroids) coherent with the Ni (α) matrix as depicted in the micrograph of Fig.…”
Section: Precipitations In the Ni (α) Solid Solutionsupporting
confidence: 86%